1995
DOI: 10.1159/000139336
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoinhibitory Effect of Estradiol in Guinea Pig Urinary Bladder Smooth Muscles

Abstract: The mechanoinhibitory effect of estradiol on the myogenic activity of guinea pig urinary bladder detrusor muscles was studied. In detrusor muscles tonically contracted with 80 mmol/l KCl, 17β-estradiol and the nonestrogenic isomer 17α-estradiol at 30 µmol/l reduced the contraction by 64 ± 3 and 59 ± 1 %, respectively. In detrusor muscles maintained in Ca2+-free media and depolarized with 80 mmol/l KCl, the contractile response of muscles to the reintroduction of Ca2+ was inhibited in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
1
23
1
Order By: Relevance
“…However, the rise in [Ca 2+ ] i reported by Rusko et al [62] was small, despite the high steroid concentration, and it seems doubtful whether an elevation in [Ca 2+ ] i alone accounts for regulation of regional blood flow by oestrogens. As this effect has also been observed in rabbit basilar artery smooth muscle [64] and guinea pig detrusor muscle [65], it may represent a general action of sex steroids on K + channels. As this effect has also been observed in rabbit basilar artery smooth muscle [64] and guinea pig detrusor muscle [65], it may represent a general action of sex steroids on K + channels.…”
Section: Non-genomic Actions Of Sex Steroids In Cultured Endothelial supporting
confidence: 61%
“…However, the rise in [Ca 2+ ] i reported by Rusko et al [62] was small, despite the high steroid concentration, and it seems doubtful whether an elevation in [Ca 2+ ] i alone accounts for regulation of regional blood flow by oestrogens. As this effect has also been observed in rabbit basilar artery smooth muscle [64] and guinea pig detrusor muscle [65], it may represent a general action of sex steroids on K + channels. As this effect has also been observed in rabbit basilar artery smooth muscle [64] and guinea pig detrusor muscle [65], it may represent a general action of sex steroids on K + channels.…”
Section: Non-genomic Actions Of Sex Steroids In Cultured Endothelial supporting
confidence: 61%
“…To our knowledge, this is the first report of estrogen influencing sodium current kinetics. Other studies, however, have shown that estrogen modifies sodium current densities in the myometrium (Boyle et al, 1987;Inoue and Sperelakis, 1991) and potassium and /or calcium currents in smooth muscle of the bladder (Yasay et al, 1995), arteries (White et al, 1995), and myometrium (Erulkar et al, 1994;Yamamoto, 1995), and in neurons of the hippocampus (Joels and Karst, 1995), hypothalamus (Lagrange et al, 1995), and neostriatum (Mermelstein et al, 1996). In a case that seems analogous to the opposing actions of estrogen and androgen on electrocytes, Erulkar et al (1994) showed that estrogen and progesterone affect the myometrial potassium channel kinetics in opposite ways: estradiol decreases whereas progesterone increases the time constant of decay of the outward potassium current.…”
Section: Mechanism Of Estrogen Effects On Electrocyte Biophysical Promentioning
confidence: 91%
“…It has been suggested that the transcription factor known as nuclear factor of activated T cells (NFATc3) regulates UBSM contractility predominantly through an NFATc3-dependent increase in BK channel activity (82). In guinea pig UBSM, BK channels can potentially be activated by 17␤-estradiol, leading to UBSM relaxation, but the mechanism of this BK channel modulation by estrogens requires further investigation (158). A recent study revealed that UBSM BK channels are molecular targets for ethanol at physiologically relevant blood alcohol content levels (87).…”
Section: Ubsm Bk Channel Regulation By Other Mechanisms and Substancesmentioning
confidence: 99%